The lost - Patterson, James, 1947-; Raymond, Emily, 1972- (Patterson, James, 1947- Witch & wizard novels., 2015)
Magical teen siblings, the wizard Whit Allgood and his witch sister Wisty Allgood, used to use their powers to help and heal their city. But now they struggle against a mounting public opposition to magic and a brutal crime wave led by a powerful wizard intent on ruling the city.